Pentingnya Keselamatan, Kesehatan Kerja Dan Jiwa Kewirausahaan Bagi Warga Rw.15 Tambak Lorok Kel. Tanjung Emas Kec. Semarang Utara, Kota Semarang - Adenanthera Lesmana Dewa; Lisda Rahmasari; Iwan Mahendro (Pusat Riset dan Inovasi Nasional, 2021)
Universitas Maritim AMNI carried out community service activities at Tambak Lorok to support the government of Semarang program. It is not only students/cadets and lecturers who carry out community service activities but also the surrounding community. They are very enthusiastic in participating in implementing various program activities carried out at Tambak Lorok . The method of implementing this activity uses a direct socialization and training approach , observation, interviews and literature studies. Socialization and training materials on efforts to increase fishing yields to increase fishing family income. The observation was held in Tambak Lorok . The data collection was carried out through interview methods and as a reference for implementing community service activities was using the literature study method. The success of these program was indicated by improve the healthy lifestyles and increase the income of the Tambak Lorok Community.